Traumatic atlantoaxial subluxation associated with congenital aplasia of the odontoid process of the axis in an English Springer Spaniel. Issue 1 (8th March 2021) - Gilbert, Emma; Driver, Colin
Abstract: We describe a three‐year‐old English Springer Spaniel presented with peracute and traumatic onset of cervical spinal cord signs of non‐ambulatory tetraparesis and bilateral Horner's syndrome. MRI and CT revealed aplasia of the odontoid process, dramatic dorsal displacement of the axis and marked compression of the spinal cord with changes consistent with oedema and inflammation. Surgical reduction of the vertebrae and atlantoaxial arthrodesis was successful, with recovery of ambulation over six weeks. A follow‐up CT six weeks later confirmed stability of the implants. The dog is clinically stable 19 months on. Traumatic atlantoaxial subluxation associated with congenital dysplasia of the odontoid process is rarely reported in medium breed dogs.